EFEKTIFITAS METODE PEMBELAJARAN TAHSIN AL-QUR’AN TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN PADA MAHASISWA/I AKPER MALAHAYATI MEDAN - MULIANI NASUTION (LP2MTBM MAKARIOZ, 2022)
This study aims to determine the learning method of tahsin and the ability to read the Qur'an as well as the effectiveness of learning tahsin on the ability to read the Qur'an of students, namely: Effective. This type of research when viewed from the object is a type of field research (field research) because the data required is obtained from the field. In analyzing the data, this research used an experimental method with a posttest only control design, namely placing the research subjects into two groups (classes) which were divided into an experimental class and a control class. To obtain the validity of the data, the researcher uses a data triangulation technique, namely a data validity checking technique that utilizes something other than the data for checking purposes or as a comparison of the data. In addition, this research was also carried out using a qualitative approach, namely a method based on scientific or scientific methods because it has fulfilled scientific principles, namely concrete/empirical, objective, measurable, rational and systematic. So to get valid data, the researcher uses in-depth interviews and observations will be analyzed through descriptive analysis, namely the data obtained, studied, classified and analyzed in depth, then concluded.